A Psychoanalytical Analysis of Scopophilia in Seamus Heaney’s Selected Poems - Dana Shamsaddin Muhammed Sharif; Abdelrahman Jalal Othman (International Journal of Social Sciences & Educational Studies, 2023)
Seamus Heaney is widely seen as one of the significant Irish writers of the twentieth century who authored and edited a number of well-known books and collections. Heaney’s work reflected concepts of political violence, sexual desire, landscape, childhood memories and myths. Research has been conducted on the mentioned concepts. However, research about Heaney’s concept of scopophilia is scarce, despite its wide depiction in Heaney’s poetry. Therefore, this study investigates Heaney’s stance as an Irish scopophilic in his poems. To explore this, the present research views Heaney’s work from a psychoanalytical perspective. To examine the texts, this study employed a critical qualitative approach that entailed a close reading of Heaney’s selected poems. The analysis was supported by background research of the context of the poems. This study mainly found that sex and power manifested through scopophilia are recurrent phenomena which motivate human ambitions and lead to world problems and suffering.